Thermal debonding of inclusions in compacted graphite iron: Effect of matrix phases. (September 2022) - Nektaria Palkanoglou, Evangelia; Baxevanakis, Konstantinos P.; Silberschmidt, Vadim V.
Highlights: Effect of matrix phases on graphite debonding under thermal load is studied. Microstructure-based modelling and homogenisation approach employed. Shielding effect of pearlitic matrix in interfacial debonding is confirmed. Inadequate results when using temperature-independent constitutive parameters. Abstract: This paper investigates graphite decohesion as the primary fracture mechanism of compacted graphite iron (CGI) subjected to thermal load. Despite CGI's extensive industrial use and considerable research on its mechanical behaviour, thermal debonding is not yet fully understood, nor is the influence of matrix phases on it. After thermal cycling to confirm the occurrence of the phenomenon, a numerical approach is developed: a 2D unit cell is constructed, with a single graphite particle, represented as an ellipse embedded in a metallic matrix. The inclusion is surrounded by an extra layer that accounts for either pearlite or ferrite, in order to study their effect on thermal debonding. An elastoplastic behaviour is assumed for all constituents, described with a classical J2 flow theory of plasticity, and the models are analysed employing a finite-element approach. The proposed numerical strategy focuses on the influence of matrix phases on thermal debonding, identifying numerical schemes to assess it. The obtained results can provide significant knowledge on the response of CGI to thermal load at the microscale, contributing to the understanding of its macroscopic thermomechanical behaviour.